Incidence of pancreatitis, secondary causes, and treatment of patients referred to a specialty lipid clinic with severe hypertriglyceridemia: a retrospective cohort study - Francis Gordon A; Frohlich Jiri; Taraboanta Catalin; Al-Sarraf Ahmad; Sandhu Supna (Lipids in Health and Disease, 2011)
Abstract Background Severe hypertriglyceridemia (HTG) is one cause of acute pancreatitis, yet the level of plasma triglycerides likely to be responsible for inducing pancreatitis has not been clearly defined. Methods and Results A retrospective cohort study was conducted on patients presenting non-acutely to the Healthy Heart Program Lipid Clinic at St. Paul's Hospital with a TG level > 20 mM (1772 mg/dl) between 1986 and 2007. Ninety-five patients with TG > 20 mM at the time of referral were identified, in who follow up data was available for 84. Fifteen patients (15.8%), with a mean outpatient TG level of 38.1 mM, had a history of acute pancreatitis. Among 91 additional patients with less severe HTG, none had a history of pancreatitis when TG were between 10 and 20 mM. Among patients with TG > 20 mM on presentation, 8 (8.5%), with a mean TG level of 67.8 mM, exhibited eruptive xanthomata. A diet high in carbohydrates and fats (79%) and obesity (47.6%) were the two most frequent secondary causes of HTG at initial visit. By 2009, among patients with follow up data 53% exhibited either pre-diabetes or overt Type 2 diabetes mellitus. Upon referral only 23 patients (24%) were receiving a fibrate as either monotherapy or part of combination lipid-lowering therapy. Following initial assessment by a lipid specialist this rose to 84%, and remained at 67% at the last follow up visit. Conclusions These results suggest hypertriglyceridemia is unlikely to be the primary cause of acute pancreatitis unless TG levels are > 20 mM, that dysglycemia, a diet high in carbohydrates and fats, and obesity are the main secondary causes of HTG, and that fibrates are frequently overlooked as the drug of first choice for severe HTG.